Ⅳ期肺腺癌二线EGFR-TKIs治疗失败后预后因素分析 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: The prognostic factors and salvage therapy after the failure of epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) therapy have brought concerns. This study aims to analyze retrospectively the clinical data of patients with advanced lung adenocarcinoma and explore their prognostic factors. METHODS: Patients with integral clinic dates and staged Ⅳ lung adenocarcinoma with performance status (PS) scores from 0 to 2 were enrolled between January 2009 and February 2012 and followed up until death. The primary endpoint was survival time after the failure of EGFR-TKI therapy. RESULTS: A total of 81 patients were enrolled into the study, and the median overall survival time was 9.6 months (Q(L)-Q(U): 5.4-19.2). Univariate analysis showed that PS score, metastatic status, and the presence of plural effusion were significantly correlated with patient survival time (P < 0.05), whereas normal levels of carcinoembryonic antigen after EGFR-TKI therapy and history of operation showed a trend towards longer survival time. Multivariate analysis showed that the PS score, metastatic status, and plural effusion are independent prognostic factors for advanced adenocarcinoma after the failure of targeted therapy (P < 0.05). CONCLUSION: A PS score from 0 to 1, single metastasis, and none or less plural effusion may attribute to the good outcome of stage Ⅳ lung adenocarcinoma and should further undergo chemotherapy.